A Case Report of Clinical Characteristics of Deficiency of Adenosine Deaminase 2 with Pancytopenia - ZHANG Caihui; LIU Liying; ZHANG Zhenjie; WANG Wei; MA Mingsheng; SONG Hongmei (罕见病研究)
Deficiency of adenosine deaminase 2(DADA2) is a rare monogenic autoinflammatory disorder caused by genetic variations in the ADA2 gene. The disease has complex clinical manifestations. The hematological involvement is infrequent in the disease. Therefore, the disease is frequently wrongly diagnosed and missed diagnoses. This article reports a case of a child patient with DADA2 who was admitted to the Peking Union Medical College Hospital. The child had aplastic anemia. After inadequate response to treatment with glucocorticoids, cyclosporine, and various supportive measures, the patient exhibited pancytopenia. Genetic testing showed a novel homozygous mutation in the ADA2 gene (NM_001282225.2:c.712_750dupGACAACGTGCTCTACATGGAGATCAGAGCCAGGCTGCTG), with reduced ADA2 levels in peripheral blood. Based on the testing results and clinical manifestations, the patient was diagnosed DADA2. Genetic testing and monitoring of ADA2 levels proved helpful in the early diagnosis of DADA2. Treatment protocol should base on the disease phenotype and severity, and include glucocorticoids, immunosuppressants, biological agents, and hematopoietic stem cell transplantation.